Pengaruh Restrukturisasi Pembiayaan Murabahah Terhadap Non Performing Financing Pada BPRS Al-Ihsan Bandung - Azis Zaelani Setiawan; Ade Ali Nurdin; Dadang Hermawan (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study is to find out 1) The implementation of the problematic murabahah financing restructuring policy in PT. BPRS Al-Ihsan Bandung. 2) Constraints on the implementation of the murabahah financing restructuring policy are problematic in PT. BPRS Al-Ihsan Bandung. 3) The effect of restructuring on non-performing financing. This type of research is descriptive with a quantitative approach. The research informants were 2 employees of PT. BPRS Al-Ihsan Bandug. Data collection techniques using interviews and financial statements of PT. BPRS Al-Ihsan Bandung, which is published by the financial services authority and its analytical tools, uses a simple linear regression test. Based on the results of research that has been carried out by researchers, it can be concluded that namely: 1) The policy of restructuring murabahah financing is problematic in PT. BPRS Al-Ihsan Bandung with the aid of cenverting or reorganizing the financing length and the veriety of installments is reduced by the previous analysis before being received by the analysis department and the customer makes an application letter to be able to restructure the financing so that later the payment of installments of its obligations can return smoothly. 2) Constraints on the implementation of the murabahah financing restructuring policy are problematic in PT. BPRS Al-Ihsan Bandung the first problem is that the customer's dishonesty to pay his obligations to the bank, the second customer does not increase the AJB to SHM so that legally the bank is difficult to take legal action to confiscate its collateral and thirdly, there are still some customers who have been restructured but are still unable to pay due to unwanted situations and conditions such as layoffs, covid19. 3) The effect of restructuring on non-performing financing, the decreasing restructuring will affect the increase in non-performing financing and the total amount of influence (R Square) of restructuring on non-performing financing is 40.7% while 59.3% of non-performing financing is influenced by other variables not studied. Keywords: Restructuring, Non Performing Financing